Listening to Athletes' Voices: National Team Athletes' Perspectives on Advancing Safe Sport in Canada - Willson, Erin; Kerr, Gretchen; Battaglia, Anthony; Stirling, Ashley (Frontiers in Sports and Active Living, 2022)
With increased media scrutiny, public awareness, and research on the prevalence of maltreatment experiences in sport, sport organizations have faced increased pressures to combat unsafe practices in sport. A consequence has been the emergence of the Safe Sport movement whereby organizations including the International Olympic Committee, Safe Sport International, US Center for SafeSport, Sport Canada, and others, have developed policies, initiatives, and education intended to create safer sport environments for all participants. Most of these policies have been implemented using a top-down approach, driven by government officials and sport leaders. However, if safe sport initiatives are to benefit athletes, consideration and incorporation of athletes' perspectives in the development and implementation of initiatives are imperative. The purpose of this study, therefore, was to examine athletes' perspectives on the challenges and recommendations to advancing safe sport. As part of a large-scale survey of current and retired Canadian National Team Athletes' experiences of maltreatment, open-ended questions were asked about athletes' recommendations and considerations for safe sport. Responses to these questions (n = 386) were analyzed using thematic analysis. According to the participants, barriers and challenges to safe sport included emphasizing performance excellence at-all-costs, normalization and complicity of harm, lack of attention to equity, diversity and inclusion, a culture of fear and silence, and a lack of trust in organizations to handle cases of harm. In an effort to advance safe sport, participants recommended prioritizing holistic athlete development, improving and strengthening accountability measures, implementing an independent 3rd party for disclosure, reporting and support, increased attention to equity, diversity and inclusion, stakeholder education, prohibition of sexual relations between athletes and those in positions of power and authority, and adoption of a broader perspective of harms and perpetrators. Findings are interpreted and critiqued in light of previous literature and recommendations for future research and practice are suggested.